Health Literacy of Children among Parents in "Puspa Sehat UNPAD" Daycare During COVID-19 Endemic Period - Alfianita, Dita Ayu; Khadijah, Ute Lies Siti; Kurniasih, Nuning (Indonesian Journal of Librarianship, 2023)
Abstract Background: Early-age children are lacking the ability to independently maintain health, indicating the crucial role of parents in ensuring well-being. Objective: This study aimed to assess the literacy skills of parents at Puspa Sehat UNPAD in obtaining, deciding, applying, and presenting health-related information. Method: A case study with a qualitative method was applied through interviews, literature review, observation, and data triangulation. Results: The results showed that parents at Puspa Sehat UNPAD can identify health issues and information requirements concerning dental health, child nutrition, and skin health. Furthermore, information was obtained from various channels such as Google, Instagram, journals, healthcare professionals, and consultations. In making informed decisions, it was necessary to read, listen, and observe relevant and credible sources, such as healthcare professionals. Health information was applied by visiting a doctor based on recommendations, selecting nutritionally appropriate foods, and purchasing prescribed skin medications. It was also presented verbally and through social media such as WhatsApp. Conclusion: To maintain the health of children, parents at Puspa Sehat UNPAD demonstrated fairly good health literacy skills. Keywords: Health Literacy; Early-age Children; Puspa Sehat UNPAD Daycare